THE ESSENCE OF COMIC TEXT AND TRANSLATION CONCEPTS - E’zozakhan Abdukhamidova (Western European Studies, 2024)
This article highlights the uniqueness of comic texts in English and Uzbek languages, linguistic and cultural aspects of children’s anecdotes.
Keywords: humor; comedy; anecdote; folklore